Ejercicio 66

Comparte esto 👍👍
CAPITULO VI

PRODUCTOS Y COCIENTES NOTABLES
Ejercicio 66
Desarrollar:
  1. (a+2 ) 3 = ( a ) 3 +3 ( a ) 2 ( 2 ) +3( a ) ( 2 ) 2 + ( 2 ) 3 = a 3 +6 a 2 +12a+8
  2. (x1 ) 3 = ( x ) 3 3 ( x ) 2 ( 1 ) +3( x ) ( 1 ) 2 ( 1 ) 3 = x 3 3 x 2 +3x1
  3. (m+3 ) 3 = ( m ) 3 +3 ( m ) 2 ( 3 ) +3( m ) ( 3 ) 2 + ( 3 ) 3 = m 3 +9 m 2 +27m+27
  4. (n4 ) 3 = ( n ) 3 3 ( n ) 2 ( 4 ) +3( n ) ( 4 ) 2 ( 4 ) 3 = n 3 12 n 2 +48n64
  5. (2x+1 ) 3 = (2x ) 3 +3 (2x ) 2 ( 1 ) +3(2x ) ( 1 ) 2 + ( 1 ) 3 =8 x 3 +12 x 2 +6x+1
  6. (13y ) 3 = ( 1 ) 3 3 ( 1 ) 2 (3y ) +3( 1 ) (3y ) 2 (3y ) 3 =19y+27 y 2 27 y 3
  7. (2+ y 2 ) 3 = ( 2 ) 3 +3 ( 2 ) 2 ( y 2 ) +3( 2 ) ( y 2 ) 2 + ( y 2 ) 3 =8+12 y 2 +6 y 4 + y 6
  8. (12n ) 3 = ( 1 ) 3 3 ( 1 ) 2 (2n ) +3( 1 ) (2n ) 2 (2n ) 3 =16n+12 n 2 8 n 3
  9. (4n+3 ) 3 = (4n ) 3 +3 (4n ) 2 ( 3 ) +3(4n ) ( 3 ) 2 + ( 3 ) 3 =64 n 3 +144 n 2 +108n+27
  10. ( a 2 2b ) 3 = ( a 2 ) 3 3 ( a 2 ) 2 (2b ) +3( a 2 ) (2b ) 2 (2b ) 3 = a 6 6 a 4 b+12 a 2 b 2 8 b 3
  11. (2x+3y ) 3 = (2x ) 3 +3 (2x ) 2 (3y ) +3(2x ) (3y ) 2 + (3y ) 3 =8 x 3 +36 x 2 y+54x y 2 +27 y 3
  12. (1 a 2 ) 3 = ( 1 ) 3 3 ( 1 ) 2 ( a 2 ) +3( 1 ) ( a 2 ) 2 ( a 2 ) 3 =13 a 2 +3 a 4 a 6